Extraction and Estimation of furfural from Decorative Plants Grown in Bangladesh (Bangladesh Journal of Scientific and Industrial Research, 2008)
An investigation on some decorative plants widely grown in Bangladesh has been carried out. The plants Mimusops elengi, Madhuca indica, Hiptage benghalensis and Polyalthia longifolia have been analyzed for their furfural contents by colorimetric spectrophotometry after hydrolysis in 13 percent HCl and extraction with 50 % ethanol. The results revealed that the furfural concentration in these plants is in the range of 3.9-10.3 percent, indicating the potential of these plants as good source of pentosans and furfural. TLC and conventional chemical test further confirmed the presence of furfural in extracted solution.Key words: Decorative plan, pentosans, furfural, TCL. Bangladesh J. Sci. Ind. Res. 42(4), 495-498, 2007